O‘ZBEK ADABIYOTIDA IT OBRAZINING IJTIMOIY-FALSAFIY VA BADIIY-ESTETIK ASOSLARI - Ashurov Bekzod Shavkatjon o‘g‘li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This article discusses the socio-philosophical and artistic-aesthetic foundations of the image of the dog in Uzbek literature, as well as their ideological-artistic features. The collection of ―Uzbek folk proverbs‖ analyzes proverbs directly related to the image of a dog. The image of a selfish, narrow-minded person as a person is revealed with the help of a dog named Koplon in Said Ahmed's story ―Koplon‖.